Цитопротективні ефекти селективних модуляторів естрогенових рецепторів за умов гіпоксії кардіоміоцитів in vitro - Павлов, Сергій Васильович; Левченко, Катерина Віталіївна; Pavlov, S. V.; Levchenko, K. V. (My University, 2016)
Мета дослідження – вивчення цитопротективної дії SERM за умов моделювання гіпоксії кардіоміоцитів in vitro. Експериментальну частину виконано на статтевозрілих білих нелінійних щурах – самцях масою 190–230 г. Гіпоксію in vitro моделювали шляхом внесення в суспензію кардіоміоцитів роз’єднувача тканьового дихання – 1-метил-4-феніл-1,2,3,6-тетрагідропіридину (МФП) у концентрації 0,6 мкмоль/л. Час інкубації – 120 хв. Досліджувані препарати (тамоксифену цитрат та референс-препарат – естрадіолу валерат) в інкубаційне середовище вносили в концентрації 10–7 моль/л. Кардіопротективні ефекти досліджуваних препаратів оцінювали за їхньою здатністю впливати на енергетичний метаболізм; зменшувати явища оксидативного стресу. Внесення в інкубаційне середовище 0,6 мкмоль/л МФП призводило до каскаду патобіохімічних змін кардіоміоцитів, характерних для гіпоксичного пошкодження тканин. Так, на 120 хв МФП- індукованої гіпоксії було зареєстровано виражений енергодефіцит, який проявлявся дисбалансом умісту в клітинах макроергічних фосфатів, а саме, статистично вірогідно зменшувалися концентрації АТФ та АДФ на тлі збільшення концентрації АМФ. Паралельно з цим на 120 хв гіпоксії в кардіоміоцитах інтенсифікувалися процеси вільнорадикального окиснення, внаслідок чого реєструвалося накопичення цито- та геномотоксичних маркерів окисного стресу – нітротирозину (НТЗ) та гомоцистеїну. Внесення до суспензій кардіоміоцитів з моделлю гіпоксії in vitro тамоксифену (10–7 моль/л) та естрадіолу (10–7 моль/л) призводило до певного обмеження оксидативного стресу, що проявлялося в статистично вірогідному зменшенні концентрації як нітротирозину, так і гомоцистеїну. Дія досліджуваних препаратів була односпрямованою, однак різного ступеня. The aim of research is to study the cytoprotective action of SERM on the cardiomyocytes’ hypoxia model in vitro. Experimental part was made on nonlinear mature white rats – males weighing 190–230 g. Hypoxia in vitro was modeled by introducing into the suspension of the cardiomyocytes of 1-methyl-4-phenyl- 1,2,3,6-tetrahydropiridin (MFD) at a concentration of 0,6 mM as tissue respiration uncoupler. Incubation time was 120 min. The studied drugs (tamoxifen citrate and reference-drug estradiol valeras) were added to the incubation medium at a concentration of 10–7 М. Cardioprotective effects of studied drugs were evaluated for their ability to influence on energy metabolism; to reduce the effects of oxidative stress. Adding 0,6 mM of MFD to the incubation medium has led to a cascade of pathobiochemical changes of cardiomyocytes characteristic for hypoxic tissue damage. Thus, for 120 min of hypoxia-induced MFD were registered the pronounced energy deficit which expressed by imbalance of macroergic phosphates content in the cells, namely statistically significant decrease in the concentration of ATP and ADP against the background of increasing of AMP concentration. Parallel to this in 120 min of hypoxia the processes of free radical oxidation were intensified in cardiomyocytes, therefore, the accumulation of cyto- and genotoxic markers (nitrotyrosine and homocysteine) of oxidative stress were recorded. Adding of tamoxifen (10–7 M) and estradiol (10–7 M) to the cardiomyocytes suspension with modeling of hypoxia in vitro has resulted in some extent the limitation of oxidative stress, which manifested in a statistically significant decrease of nitrotyrosine and homocysteine concentrations. Action of studied drugs was unidirectional, but with different degree of action. So, tamoxifen better than estradiol affects to the content of homocysteine, reducing its concentration respectively to 76 and 65 %. The reduction of nitrotyrosine in suspension of cardiomyocytes with the introduction of tamoxifen and estradiol averaged 50 %. Due to the high antioxidant activity studied drugs have improved the energy exchange of cells, increasing the content of ATP, ADP in cardiomyocytes suspension and reducing AMP content. Determined effects of tamoxifen citrate and estradiol valeras are an experimental substantiation of relevance and perceptivity for further research in this area.
Cytoprotective effects of selective modulators of estrogen receptors in hypoxia of cardiomyocytes in vitro
Keywords: кардіоміоцити; гіпоксія in vitro; селективні модулятори естрогенових рецепторів; cardiomyocytes hypoxia in vitro; selective estrogen receptor modulators